A new strategy towards spectral selectivity: Selective leaching alloy to achieve selective plasmonic solar absorption and infrared suppression. (February 2022) - Tian, Yanpei; Liu, Xiaojie; Caratenuto, Andrew; Li, Jiansheng; Zhou, Shiyu; Ran, Ran; Chen, Fangqi; Wang, Ziqi; Wan, Kai-tak; Xiao, Gang; Zheng, Yi
Abstract: Cost-effective and spectrally selective solar absorbers that possess high solar absorptance, low thermal emittance, and superior thermal stability are essential for photothermal conversion applications, e.g., industrial heating, solar desalination, photothermal catalysis, and concentrating solar power systems. Here, a new strategy using a selective leaching reaction is demonstrated for transfiguring the broad-spectrum and highly reflective aluminum alloys into plasmonic-nanostructure selective solar absorbers (PNSSAs). Enabled by surface plasmon resonance, this strategy via assembling copper nanostructured thin film on an alloy mirror yields tunable manipulation of the spectral selectivity, high and omnidirectional solar absorptance (0.94 from 0 to 60°), low thermal emittance (0.03 at 100 °C), and excellent thermomechanical stability. Featured with merits of competitive performance of spectral selectivity, the feasibility of solution-processed fabrication, and cost-effectiveness of raw materials and chemicals, selective-leaching-alloy to achieve PNSSAs is a promising and universal approach for achieving high photothermal efficiency (85%) of solar thermal energy harvesting. The compatibility of this strategy with other metal alloys, such as steel and superalloys, extends its applications to fabricating mid- and high-temperature selective solar absorbers. Graphical abstract: Highlights: Validated a strategy of transfiguring metal alloys into selective solar absorbers. Tunable spectral selectivity via surface plasmon resonance of copper nanostructure. High solar absorptance and low thermal emittance are demonstrated. Selective leaching strategy can be applied on other refractory metals.